Autonomic effects of intraventricular extension in intracerebral hemorrhage - Sykora, Marek; Steiner, Thorsten; Poli, Sven; Rocco, Andrea; Diedler, Jennifer (Neurocritical care, 2012)
BackgroundAutonomic dysfunction after stroke is common and relates to unfavorable outcome. The pathophysiology of autonomic impairment after intracerebral hemorrhage (ICH) is unknown. This study examined the relationship between intraventricular hemorrhage extension (IVH) and autonomic dysregulation after ICH.MethodsWe examined the autonomic modulation using the cross-correlational time-sequence baroreflex sensitivity (BRS) in 68 ICH patients with and without IVH. Localization and extent of IVH based on the LeRoux score, hydrocephalus, hematoma volume, initial stroke severity and baseline demographic, clinical, and biochemical parameters were included in the analysis.ResultsIVH was present in 36 (52.9%) of patients. BRS was significantly lower in patients with IVH compared to those without IVH (BRS 2.35 vs. 3.5 ms/mmHg, P = 0.03). Patients with IVH including third and fourth ventricle had significantly lower BRS than patients with IVH in lateral ventricles (2.1 vs. 5.9 ms/mmg, P = 0.008) or patients without IVH (2.1 vs. 3.5 ms/mmHg, P = 0.003). There was no significant difference in BRS between patients with IVH in the lateral ventricles and patients without IVH (median BRS 5.9 vs. 3.5 ms/mmHg, P = 0.36). The amount of IVH in the third and fourth ventricle inversely correlated with decreased BRS (r = −0.43, P < 0.001). BRS did not correlate with initial hydrocephalus, hemorrhage volume, NIHSS score at admission, etiology of the ICH or parenchymal localization of the ICH.ConclusionsHematoma extension to the third and fourth ventricle seems to cause profound autonomic dysregulation, possibly contributing to poor outcome. Patients with IVH in this location should be monitored vigorously to prevent and treat complications of autonomic failure.
Published online: 6 October 2011
Gesehen am 21.06.2018